Gini regressions and heteroskedasticity - Arthur Charpentier; Ndéné Ka; Stéphane Mussard; Oumar Hamady Ndiaye (Econometrics, 2019)
We propose an Aitken estimator for Gini regression. The suggested A -Gini estimator is proven to be a U-statistics. Monte Carlo simulations are provided to deal with heteroskedasticity and to make some comparisons between the generalized least squares and the Gini regression. A Gini-White test is proposed and shows that a better power is obtained compared with the usual White test when outlying observations contaminate the data.
Keywords: C14; C3; 330; Gini; heteroskedasticity; jackknife; U-statistics